Control Strategies for Modular Multilevel Converters Driving Cage Machines - Diaz-Diaz, M (Institute of Electrical and Electronics Engineers Inc., 2018)
The Modular Multilevel Converter has emerged as a suitable topology for high power drive applications. However, high voltage fluctuations could appear in the converter capacitors depending on the operating drive point. Then, mitigating signals, which lead to oversized dimensioning, are required to keep the capacitor voltages within an acceptable range. In this paper, a new control scheme is proposed to regulate the capacitor voltages within a desired margin reducing the mitigating signals as the machine frequency increases. The effectiveness of the proposed control strategy is validated with a laboratory-based prototype composed of eighteen power cells, feeding a vector-controlled induction machine. © 2017 IEEE.